Palladium‐Catalyzed Allylic Alkylation Reactions of Glycolates as a Tool for the Synthesis of Functionalized α‐Hydroxy Esters. Issue 26 (3rd August 2015) - Kiefer, Alexander; Gawas, Dnyaneshwar; Kazmaier, Uli
Abstract: Deprotonated tert ‐butyl glycolates were found to be suitable nucleophiles for Pd‐catalyzed allylic alkylation reactions to generate γ, δ‐unsaturated α‐hydroxy acid derivatives. This protocol is suitable for the introduction of different side chains and includes stannylated ones. These can be subjected to further cross‐coupling reactions, which gives access to a wide range of structural motifs. Abstract : Deprotonated tert ‐butyl glycolates are suitable nucleophiles for Pd‐catalyzed allylic alkylation reactions that generate γ, δ‐unsaturated α‐hydroxy acid derivatives. Stannylated derivatives can be subjected to further modifications.